Implementasi Algoritma Genetika Dalam Penentuan Jadwal Perkuliahan Berdasarkan Kebutuhan Pengguna (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2022)
Education is an important thing in life. In practice, education consists of teachers and students. A teacher teaches a subject to students. Students are taught by several or more teachers. There is a provision in which a class of students can only receive one subject at a time. Teachers can also only teach one subject at a time. This requires a system that is used to regulate so that these provisions can be fulfilled without ignoring other provisions. The system used to manage these problems is a subject scheduling system. This system regulates the class placement of students with the subjects they study. In manual implementation, the process is very inefficient in terms of time, human resources and thought power. The method that can be used to solve this problem is the genetic algorithm. A genetic algorithm is a heuristic method or procedure inspired by the natural selection process. Genetic algorithms are generally used to produce high-quality solutions to problems in the form of optimization and search by relying on biologically inspired operators such as mutation, crossbreeding, and selection